A Resonant Coupling Power Transfer System Using Two Driving Coils - Changping Li (603133) (2019)
This paper presents a resonance-based wireless power transfer (R-WPT) system using two multi-layer multi-turn inductor coils on the transmission side and a third coil on the receiver side. We theoretically characterized and optimized the system in terms of quality factor (Q factor) of the coils and power transfer efficiency (PTE). In our R-WPT prototype, the alternating currents (AC) were simultaneously applied to two transmitter coils, which, in turn, transferred power wirelessly to the secondary coil with a 3-mm radius on the receiving end. Owing to the optimization of the inductive coils, all of the coils achieved the highest Q-factor and PTE at the resonance frequency of 2.9 MHz, and the transfer distance could be extended up to 30 mm. The results show that the PTE was greater than 74% at a separation distance of 5 mm and about 38.7% at 20 mm. This is distinctly higher than that of its 2 and 3-coil counterparts using only one driving coil. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en12152914